Molecular characterization of novel and rare DNA variants in patients with galactosemia - Maroulis, Vasileios; Agathangelidis, Andreas; Skouma, Anastasia; Sdogou, Triantafyllia; Papadakis, Manoussos N.; Papakonstantinou, Evangelos; Girginoudis, Panagiotis; Vorgias, Constantinos E.; Aleporou, Vassiliki; Kollia, Panagoula (Frontiers in Genetics, 2023)
Introduction: Galactosemia is an inherited disorder caused by mutations in the three genes that encode enzymes implicated in galactose catabolism. Currently, the only available treatment for galactosemia is life-long dietary restriction of galactose/lactose, and despite treatment, it might result in long-term complications. Methods: Here, we present five cases of newborn patients with elevated galactose levels, identified in the context of the newborn screening program. Genetic analysis concerned a next generation sequencing (NGS) methodology covering the exons and adjacent splice regions of the GALT, GALK1, and GALE genes. Results: Our approach led to the identification of eight rare nonsynonymous DNA variants. Four of these variants, namely, p.Arg204Gln and p.Met298Ile in GALT, p.Arg68Leu in GALK1, and p.Ala180Thr in GALE, were already recorded in relevant databases, yet their clinical significance is uncertain. The other four variants, namely, p.Phe245Leu in GALT, p.Gly193Glu in GALK1, and p.Ile266Leu and p.Ala216Thr in the GALE gene, were novel. In silico analysis of the possible effect of these variants in terms of protein function and stability was performed using a series of bioinformatics tools, followed by visualization of the substituted amino acids within the protein molecule. The analysis revealed a deleterious and/or destabilizing effect for all the variants, supported by multiple tools in each case. Discussion: These results, given the extreme rarity of the variants and the specific phenotype of the respective cases, support a pathogenic effect for each individual variant. Altogether, our study shows that targeted NGS methodologies may offer a time- and cost-effective approach for the genetic investigation of galactosemia and can assist in elucidating the complex genetic background of this disorder.